Skin-care sunscreen lotion as well as preparation method and application thereof
By using xanthan gum and 3,4-dihydroxyphenylglycine, the adhesion and network structure of sunscreen are enhanced, and the problem of the sunscreen components of traditional sunscreen is easily fallen off, achieving higher durability and protective effects.
Patent Information
- Application Number
- CN202411944218.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional sunscreen milk is prone to falling off when swimming, sweating a lot or rubbing external clothes, and has poor durability and protective effect.
The adhesive stabilizer is prepared by xanthan gum and 3,4-dihydroxyphenylglycine. Through esterification and oxidation reactions, the adhesion and complexity of the network structure of xanthan gum are enhanced, and chelated with sunscreen components such as titanium dioxide and zinc oxide to fix it on the skin surface.
It improves the durability and protective effect of sunscreen, enhances adhesion and anti-shrink performance, reduces the degradation of adhesion due to water absorption, and significantly improves the sunscreen effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, in particular to a skin care sunscreen lotion and a preparation method and application thereof. Background Art
[0002] Sunscreen, as an indispensable part of modern skin care procedures, is increasingly recognized and valued by consumers. This is because ultraviolet rays can not only cause sunburn and redness of the skin, but long-term accumulation may also cause more serious skin problems, such as sun spots, skin aging, deepening wrinkles, and even increase the risk of skin cancer. Therefore, sunscreen is a must-have product for modern people to resist ultraviolet rays and maintain skin health. However, traditional sunscreens are prone to shedding of sunscreen components such as titanium dioxide and zinc oxide when swimming, sweating heavily, or rubbing against external clothing, and have poor durability and protective effects. In view of this, we propose a skin care sunscreen lotion and a preparation method and application thereof. Summary of the invention
[0003] The object of the present invention is to provide a skin care sunscreen lotion and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0004] To achieve the above object, on the one hand, the present invention provides a method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 15-22 parts by weight of cyclopentasiloxane, 5-8 parts by weight of capric triglyceride, 2-4 parts by weight of phytosterol esters, 3-5 parts by weight of titanium dioxide nanoparticles, 1-3 parts by weight of zinc oxide nanoparticles, 4-6 parts by weight of octocrylene, 1-3 parts by weight of avobenzone, 32-38 parts by weight of deionized water, 3-8 parts by weight of glycerin, 1-2 parts by weight of sodium hyaluronate, 1-3 parts by weight of witch hazel extract, 0.1-0.5 parts by weight of ascorbic acid, 5-10 parts by weight of gum arabic, 1.5-4.5 parts by weight of acrylate copolymer, 1-5 parts by weight of viscosity stabilizer, and 2-6 parts by weight of citric acid; S1.2, preparing active ingredient microcapsules by spray drying method using gum arabic as wall material and ascorbic acid as core material; S1.3, heating the oil phase component in a heating container to 30-40°C to obtain an oil phase component mixture, and stirring the water phase component at room temperature to obtain a water phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 2000-3000rpm to form a preliminary emulsion, and then process it through a dynamic continuous homogenizer. Set the operating pressure to 150-200bar. After cooling the emulsion to 25-30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers, adjust the pH to 5.5-6.0 with citric acid, and use an automated filling line to fill the product into pre-sterilized packaging containers. Attach labels and indicate product information to obtain a skin care sunscreen lotion.
[0005] Preferably, in S1.2, the specific steps for preparing the active component microcapsules are: Gum arabic is dissolved in water to form a wall material solution with a mass fraction of 30-40%, and then ascorbic acid is added. After stirring to ensure that the two are fully mixed, the solution is passed through a filter screen of 80-100 mesh, and then the spray dryer is started. The inlet air temperature is set to 160-180°C, the outlet air temperature is set to 70-90°C, the feed rate is set to 20-30mL / min, and the atomization pressure is set to 0.3-0.5MPa. The microcapsules are collected and cooled naturally to obtain active component microcapsules.
[0006] Preferably, in S1.3, the oil phase components include cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone, and the water phase components include deionized water, glycerin, sodium hyaluronate and witch hazel extract.
[0007] Preferably, the steps for preparing the viscosity stabilizer are specifically as follows: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a thermostatic oil bath that has been preheated to 50-60°C, turn on the magnetic stirrer, and react for 2 -3h. After the reaction is completed, the round-bottom flask is taken out and cooled to room temperature. Then, a sodium bicarbonate aqueous solution is added, and the mixture after the reaction is poured into a dialysis bag with a molecular weight cutoff range of 1000-2000Da, and dialyzed in deionized water for 72-75h. During this period, the deionized water is replaced every 12-24h. Then, a rotary evaporator is used to remove moisture, and the temperature is set to 30-40°C and the vacuum degree is set to 0.05-0.08MPa. The residue is then transferred to a freeze dryer at minus 40-50°C for drying to obtain a viscous stabilizer.
[0008] Xanthan gum has a good thickening effect, which gives the sunscreen an appropriate texture, making it easy to apply and not prone to flowing. It also helps to form a protective film to help active ingredients better adhere to the skin surface, thereby increasing the durability of the sunscreen effect. Since xanthan gum is a high molecular weight polysaccharide containing multiple hydroxyl groups, it can form hydrogen bonds with polar groups on the skin surface, thereby adhering to the skin surface. However, these forces are formed by non-covalent bonds and rely solely on physical adsorption, making it difficult to remain on the skin surface for a long time, especially when swimming or sweating profusely. The presence of water molecules will affect the force of its hydrogen bonds and weaken the three-dimensional network structure formed by the xanthan gum, making it impossible for the xanthan gum to maintain its initial coverage and adhesion.
[0009] Therefore, xanthan gum is modified with 3,4-dihydroxyphenylglycine. The carboxyl group on 3,4-dihydroxyphenylglycine reacts with the hydroxyl group on xanthan gum to undergo esterification reaction, so that 3,4-dihydroxyphenylglycine is connected to the side chain of xanthan gum. Since keratin is the main protein constituting the stratum corneum of human skin, it is rich in cysteine residues. By utilizing the oxidative properties of the catechol functional group of 3,4-dihydroxyphenylglycine, it is oxidized into quinone compounds under oxygen conditions, which can react with nucleophilic groups in other molecules to chemically combine with thiol groups and amino groups on the skin surface, thereby improving its adhesion to the skin surface; at the same time, the catechol functional group can also combine with titanium dioxide and zinc oxide to form a stable metal complex. These metal ions act as bridges to connect multiple catechol functional groups together, further enhancing the complexity and firmness of the network structure and preventing water on the skin surface. When you sweat or wipe your face, titanium dioxide and zinc oxide are physically removed, which leads to a worse sun protection effect. In addition, it can also alleviate the problem of physical sunscreen molecules titanium dioxide and zinc oxide remaining on the skin surface and causing "white spots". Through the π-π stacking effect of the aromatic ring structure in the catechol functional group, it attracts other aromatic compounds, and the non-polarity of the aromatic ring itself shows a certain hydrophobicity, which helps to limit the entry of moisture into the adhesion interface and prevent the degradation of adhesion performance due to water absorption. In general, the introduction of 3,4-dihydroxyphenylglycine into xanthan gum, the quinone compounds formed by the oxidation reaction of the catechol functional group and their subsequent cross-linking, plus the cross-linking of metal ions, constructs a complex three-dimensional network, which can improve the adhesion of xanthan gum on the skin surface on the one hand, and on the other hand, it can combine with other components in the sunscreen to improve the stability of the overall structure, thereby improving the sun protection effect.
[0010] Preferably, the mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.3-0.5.
[0011] Preferably, the added amount of p-toluenesulfonic acid is 2-6% of the total mass of xanthan gum, and the mass concentration of the p-toluenesulfonic acid solution is 0.4-0.6 g / mL.
[0012] Preferably, the mass concentration of the xanthan gum solution is 0.01-0.03 g / mL.
[0013] Preferably, the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1-1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.05-0.1M.
[0014] On the other hand, the present invention provides a skin care sunscreen lotion, which is prepared by the above-mentioned preparation method of skin care sunscreen lotion.
[0015] The present invention also provides an application of a skin care sunscreen lotion, which is an application of the skin care sunscreen lotion to improve the adhesion of the skin surface.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the skin care sunscreen lotion and its preparation method and application, xanthan gum and 3,4-dihydroxyphenylglycine are used to prepare a viscosity stabilizer, 3,4-dihydroxyphenylglycine is connected to the xanthan gum through an esterification reaction, and the oxidation characteristics of the catechol functional group on the 3,4-dihydroxyphenylglycine are used to chemically combine with the thiol group and the amino group on the skin surface, thereby improving the adhesion of the xanthan gum on the skin surface and alleviating the influence of water molecules on the coverage and adhesion of the xanthan gum. The chelation effect between the catechol functional group and the metal ion is used to enhance the complexity of the xanthan gum network structure on the one hand, and on the other hand, titanium dioxide and zinc oxide can be dispersed and fixed, thereby avoiding the shedding of components caused by external scouring, and improving the durability and protective effect. At the same time, the aromatic structure of the catechol functional group can provide a certain hydrophobicity, which helps to limit the entry of water into the adhesion interface, prevent the decrease of adhesion performance due to water absorption, and thus improve the sunscreen effect. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] A method for preparing a skin care sunscreen lotion of the present invention comprises the following steps: S1.1. Weigh the following raw materials in parts by weight: 15-22 parts by weight of cyclopentasiloxane, 5-8 parts by weight of capric triglyceride, 2-4 parts by weight of phytosterol esters, 3-5 parts by weight of titanium dioxide nanoparticles, 1-3 parts by weight of zinc oxide nanoparticles, 4-6 parts by weight of octocrylene, 1-3 parts by weight of avobenzone, 32-38 parts by weight of deionized water, 3-8 parts by weight of glycerin, 1-2 parts by weight of sodium hyaluronate, 1-3 parts by weight of witch hazel extract, 0.1-0.5 parts by weight of ascorbic acid, 5-10 parts by weight of gum arabic, 1.5-4.5 parts by weight of acrylate copolymer, 1-5 parts by weight of viscosity stabilizer, and 2-6 parts by weight of citric acid; S1.2, preparing active ingredient microcapsules by spray drying method using gum arabic as wall material and ascorbic acid as core material; S1.3, heating the oil phase component in a heating container to 30-40°C to obtain an oil phase component mixture, and stirring the water phase component at room temperature to obtain a water phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 2000-3000rpm to form a preliminary emulsion, and then process it through a dynamic continuous homogenizer. Set the operating pressure to 150-200bar. After cooling the emulsion to 25-30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers, adjust the pH to 5.5-6.0 with citric acid, and use an automated filling line to fill the product into pre-sterilized packaging containers. Attach labels and indicate product information to obtain a skin care sunscreen lotion.
[0019] Embodiment 1: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 22 parts by weight of cyclopentasiloxane, 8 parts by weight of triglyceride of capric acid, 4 parts by weight of phytosterol esters, 5 parts by weight of titanium dioxide nanoparticles, 3 parts by weight of zinc oxide nanoparticles, 6 parts by weight of octocrylene, 3 parts by weight of avobenzone, 38 parts by weight of deionized water, 8 parts by weight of glycerin, 2 parts by weight of sodium hyaluronate, 3 parts by weight of witch hazel extract, 0.5 parts by weight of ascorbic acid, 10 parts by weight of gum arabic, 4.5 parts by weight of acrylate copolymer, 5 parts by weight of viscosity stabilizer and 6 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.3; the amount of p-toluenesulfonic acid added is 6% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.03 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.6 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.1 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0020] Embodiment 2: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 22 parts by weight of cyclopentasiloxane, 8 parts by weight of triglyceride of capric acid, 4 parts by weight of phytosterol esters, 5 parts by weight of titanium dioxide nanoparticles, 3 parts by weight of zinc oxide nanoparticles, 6 parts by weight of octocrylene, 3 parts by weight of avobenzone, 38 parts by weight of deionized water, 8 parts by weight of glycerin, 2 parts by weight of sodium hyaluronate, 3 parts by weight of witch hazel extract, 0.5 parts by weight of ascorbic acid, 10 parts by weight of gum arabic, 4.5 parts by weight of acrylate copolymer, 5 parts by weight of viscosity stabilizer and 6 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.4; the amount of p-toluenesulfonic acid added is 6% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.03 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.6 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.1 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0021] Embodiment 3: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 22 parts by weight of cyclopentasiloxane, 8 parts by weight of triglyceride of capric acid, 4 parts by weight of phytosterol esters, 5 parts by weight of titanium dioxide nanoparticles, 3 parts by weight of zinc oxide nanoparticles, 6 parts by weight of octocrylene, 3 parts by weight of avobenzone, 38 parts by weight of deionized water, 8 parts by weight of glycerin, 2 parts by weight of sodium hyaluronate, 3 parts by weight of witch hazel extract, 0.5 parts by weight of ascorbic acid, 10 parts by weight of gum arabic, 4.5 parts by weight of acrylate copolymer, 5 parts by weight of viscosity stabilizer and 6 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.5; the amount of p-toluenesulfonic acid added is 6% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.03 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.6 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.1 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0022] Embodiment 4: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 15 parts by weight of cyclopentasiloxane, 5 parts by weight of capric triglyceride, 2 parts by weight of phytosterol esters, 3 parts by weight of titanium dioxide nanoparticles, 1 part by weight of zinc oxide nanoparticles, 4 parts by weight of octocrylene, 1 part by weight of avobenzone, 32 parts by weight of deionized water, 3 parts by weight of glycerin, 1 part by weight of sodium hyaluronate, 1 part by weight of witch hazel extract, 0.1 part by weight of ascorbic acid, 5 parts by weight of gum arabic, 1.5 parts by weight of acrylate copolymer, 5 parts by weight of viscosity stabilizer and 2 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.5; the amount of p-toluenesulfonic acid added is 2% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.01 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.4 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1:1, and the concentration of the sodium bicarbonate aqueous solution is 0.05 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0023] Embodiment 5: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 22 parts by weight of cyclopentasiloxane, 8 parts by weight of capric triglyceride, 4 parts by weight of phytosterol esters, 5 parts by weight of titanium dioxide nanoparticles, 3 parts by weight of zinc oxide nanoparticles, 6 parts by weight of octocrylene, 3 parts by weight of avobenzone, 38 parts by weight of deionized water, 8 parts by weight of glycerin, 2 parts by weight of sodium hyaluronate, 3 parts by weight of witch hazel extract, 0.5 parts by weight of ascorbic acid, 10 parts by weight of gum arabic, 4.5 parts by weight of acrylate copolymer, 1 part by weight of viscosity stabilizer and 6 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.5; the amount of p-toluenesulfonic acid added is 6% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.03 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.6 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.1 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0024] Embodiment 6: A method for preparing a skin care sunscreen lotion, comprising the following steps: S1.1. Weigh the following raw materials in parts by weight: 22 parts by weight of cyclopentasiloxane, 8 parts by weight of capric triglyceride, 4 parts by weight of phytosterol esters, 5 parts by weight of titanium dioxide nanoparticles, 3 parts by weight of zinc oxide nanoparticles, 6 parts by weight of octocrylene, 3 parts by weight of avobenzone, 38 parts by weight of deionized water, 8 parts by weight of glycerin, 2 parts by weight of sodium hyaluronate, 3 parts by weight of witch hazel extract, 0.5 parts by weight of ascorbic acid, 10 parts by weight of gum arabic, 4.5 parts by weight of acrylate copolymer, 3 parts by weight of viscosity stabilizer and 6 parts by weight of citric acid; S1.2. Prepare active ingredient microcapsules by spray drying, using gum arabic as the wall material and ascorbic acid as the core material. The specific preparation steps are as follows: Gum arabic was dissolved in water to form a wall material solution with a mass fraction of 40%, and then ascorbic acid was added. After stirring to ensure that the two were fully mixed, the solution was passed through a 100-mesh filter, and then the spray dryer was started. The inlet air temperature was set to 180°C, the outlet air temperature was set to 90°C, the feed rate was set to 30 mL / min, and the atomization pressure was set to 0.5 MPa. The microcapsules were collected and cooled naturally to obtain active component microcapsules. The mass ratio of xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.5; the amount of p-toluenesulfonic acid added is 6% of the total mass of xanthan gum; the mass concentration of the xanthan gum solution is 0.03 g / mL; the mass concentration of the p-toluenesulfonic acid solution is 0.6 g / mL; the molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.1 M; the specific steps of preparing the viscous stabilizer are: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a constant temperature oil bath that has been preheated to 60°C and start Start the magnetic stirrer and react for 2 hours. After the reaction is completed, take out the round-bottom flask, cool it to room temperature, then add sodium bicarbonate aqueous solution, pour the reaction mixture into a dialysis bag with a molecular weight cutoff range of 1000Da, place it in deionized water for 72 hours, replace the deionized water every 24 hours, and then use a rotary evaporator to remove moisture, set the temperature to 40°C, and the vacuum degree to 0.08MPa, then transfer the residue to a freeze dryer at minus 50°C for drying to obtain a viscous stabilizer; S1.3, heating cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone in a heating container to 40° C. to obtain an oil phase component mixture, and at room temperature, stirring deionized water, glycerin, sodium hyaluronate and witch hazel extract to obtain an aqueous phase component mixture; S1.4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 3000 rpm to form a preliminary emulsion. Then, process it through a dynamic continuous homogenizer and set the operating pressure to 200 bar. After cooling the emulsion to 30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers. Use citric acid to adjust the pH to 5.5. Use an automated filling line to fill the product into pre-sterilized packaging containers, affix labels, indicate product information, and obtain a skin care sunscreen lotion.
[0025] Comparative Example 1: The method of Example 3 was adopted without adding a viscosity stabilizer.
[0026] Comparative Example 2: The method of Example 3 was adopted, and xanthan gum was directly used without modifying the xanthan gum by 3,4-dihydroxyphenylglycine.
[0027] Comparative Example 3: The method of Example 3 was adopted, and 3,4-dihydroxyphenylglycine was directly used without modifying the 3,4-dihydroxyphenylglycine by xanthan gum.
[0028] The skin care sunscreen lotion prepared by the present invention using a viscosity stabilizer, wherein the performance index inspection items and inspection standards of a skin care sunscreen lotion prepared by the preparation method of the skin care sunscreen lotion are as follows: The in vitro SPF is tested according to ISO 24444:2010 "Cosmetic sunscreen test methods - In vitro determination of ultraviolet protection factor". The in vitro SPF indicates the sun protection effect of sunscreen products. After using sunscreen, the minimum erythema dose of the skin will increase. Therefore, the SPF value is calculated according to the formula SPF=minimum erythema dose (after use) / minimum erythema dose (before use). The larger the SPF value, the better the sun protection effect. It is used to characterize the protective effect of skin care sunscreen. The artificial skin sample coated with sunscreen is sprayed with a constant water flow on the skin surface coated with sunscreen, and the SPF is also measured to characterize its water scouring resistance. The artificial skin sample coated with sunscreen is rubbed 30 times using a standard friction machine, and then its SPF value is measured to characterize its durability.
[0029] The skin care sunscreen lotions prepared in Examples 1-6 and Comparative Examples 1-3 were tested according to the above standards, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3
[0030] The above data fully demonstrates that compared with Comparative Examples 1-3, Examples 1-6 can fully demonstrate the effect of the viscosity stabilizer on the durability and protective effect of the skin care sunscreen.
[0031] Since the present invention adopts a viscous stabilizer to prepare the skin care sunscreen lotion, the viscous stabilizer effectively improves the durability and protective effect of the skin care sunscreen lotion, as follows: It can be seen from Examples 1-3 that as the proportion of the viscous stabilizer component continues to increase, the durability and protective effect of the skin care sunscreen gradually increase. Since 3,4-dihydroxyphenylglycine is introduced into xanthan gum, the complexity of the xanthan gum network structure is increased, and the catechol functional group on 3,4-dihydroxyphenylglycine has oxidizing properties and can form chemical bonds on the skin surface, thereby enhancing adhesion. In addition, the catechol functional group can also chelate with metal ions such as titanium dioxide and zinc oxide to provide stronger adhesion and further fix these sunscreen ingredients. Moreover, the xanthan gum network exhibits a certain hydrophobicity due to the introduction of an aromatic ring structure, which helps to limit the entry of moisture into the adhesion interface, thereby preventing the adhesion performance from decreasing due to water absorption. Therefore, the skin care sunscreen has good anti-scouring and anti-scratch properties.
[0032] It can be seen from Examples 3 and 4 that as the content of other components in the skin care sunscreen lotion continues to change, the durability and protective effect of the skin care sunscreen lotion do not change significantly, which means that small changes in other components in the skin care sunscreen lotion within a certain range are not sufficient to significantly affect the anti-scouring and anti-scratch properties of the skin care sunscreen lotion.
[0033] It can be seen from Examples 3, 5 and 6 that as the content of the viscous stabilizer continues to change, the durability and protective effect of the skin care sunscreen lotion continues to change, which means that the stronger the interaction between xanthan gum and 3,4-dihydroxyphenylglycine and other components, this not only increases the cross-linking density between molecules, but also enhances the stability of the entire network structure. More cross-linking points also mean that even when encountering external pressure or water washing, the ingredients in the sunscreen lotion are not easily removed or dispersed, thereby improving its durability and protective effect. The catechol functional group on the viscous stabilizer can be oxidized into quinone compounds under oxygen conditions and chemically bonded with other molecules, further enhancing the fixation and durability of the sunscreen lotion on the skin.
[0034] According to the above test experiments, the skin care sunscreen lotion prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-3, it can be seen that: In Comparative Example 1, no viscosity stabilizer was added, and the durability and protective effect of the skin care sunscreen were poor. This is because without the addition of a viscosity stabilizer, the film-forming, thickening and adhesion effects of xanthan gum were lacking, resulting in the overall components of the skin care sunscreen being relatively dispersed and not stable enough, resulting in poor durability and protective effect.
[0035] In Comparative Example 2, xanthan gum is directly used without being modified by 3,4-dihydroxyphenylglycine. The durability and protective effect of the skin care sunscreen are poor. Although xanthan gum can provide thickening and adhesion by its natural polysaccharide chain, this physical adsorption mainly relies on hydrogen bonds and other weak interaction forces, which are easily destroyed when encountering water or mechanical friction, making the overall structure of the sunscreen not stable enough, especially in terms of fixing nano-level titanium dioxide and zinc oxide. In contrast, xanthan gum modified with 3,4-dihydroxyphenylglycine can form more covalent bonds through esterification reaction, which significantly enhances the connection strength between molecules and the stability of the network structure.
[0036] Comparative Example 3 directly uses 3,4-dihydroxyphenylglycine without modifying 3,4-dihydroxyphenylglycine by xanthan gum. The durability and protective effect of the skin care sunscreen are poor. This is because although 3,4-dihydroxyphenylglycine can chelate with metal ions, 3,4-dihydroxyphenylglycine itself does not have the ability to form a complex network, and its ability to fix titanium dioxide and zinc oxide is limited. Therefore, the durability and protective effect of the skin care sunscreen are poor.
[0037] In summary, the viscous stabilizer is prepared by xanthan gum and 3,4-dihydroxyphenylglycine. The network structure of xanthan gum and the catechol functional group of 3,4-dihydroxyphenylglycine can be used to utilize the adhesion and covering power of xanthan gum itself on the one hand, and on the other hand, the catechol functional group is oxidized to quinones, which can chemically combine with thiol groups and amino groups on the skin surface, thereby improving its adhesion on the skin surface. At the same time, the catechol functional group can chelate with metal ions to stabilize the physical sunscreen components, thereby improving the durability and protective effect of the skin care sunscreen lotion, thereby effectively realizing the application of the above-mentioned skin care sunscreen lotion in improving the adhesion of the skin surface.
[0038] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a skin care sunscreen lotion, characterized in that: The steps include: S1.
1. Weigh the following raw materials in parts by weight: 15-22 parts by weight of cyclopentasiloxane, 5-8 parts by weight of capric triglyceride, 2-4 parts by weight of phytosterol esters, 3-5 parts by weight of titanium dioxide nanoparticles, 1-3 parts by weight of zinc oxide nanoparticles, 4-6 parts by weight of octocrylene, 1-3 parts by weight of avobenzone, 32-38 parts by weight of deionized water, 3-8 parts by weight of glycerin, 1-2 parts by weight of sodium hyaluronate, 1-3 parts by weight of witch hazel extract, 0.1-0.5 parts by weight of ascorbic acid, 5-10 parts by weight of gum arabic, 1.5-4.5 parts by weight of acrylate copolymer, 1-5 parts by weight of viscosity stabilizer, and 2-6 parts by weight of citric acid; S1.2, preparing active ingredient microcapsules by spray drying method using gum arabic as wall material and ascorbic acid as core material; S1.3, heating the oil phase component in a heating container to 30-40°C to obtain an oil phase component mixture, and stirring the water phase component at room temperature to obtain a water phase component mixture; S1.
4. Use a high shear mixer to slowly add the aqueous phase component mixture to the oil phase component mixture at a speed of 2000-3000rpm to form a preliminary emulsion, and then process it through a dynamic continuous homogenizer. Set the operating pressure to 150-200bar. After cooling the emulsion to 25-30°C, add active ingredient microcapsules, acrylate copolymers and viscosity stabilizers, adjust the pH to 5.5-6.0 with citric acid, and use an automated filling line to fill the product into pre-sterilized packaging containers. Attach labels and indicate product information to obtain a skin care sunscreen lotion.
2. The method for preparing the skin care sunscreen lotion according to claim 1, characterized in that: In S1.2, the specific preparation steps of the active component microcapsules are: Gum arabic is dissolved in water to form a wall material solution with a mass fraction of 30-40%, and then ascorbic acid is added. After stirring to ensure that the two are fully mixed, the solution is passed through a filter screen of 80-100 mesh, and then the spray dryer is started. The inlet air temperature is set to 160-180°C, the outlet air temperature is set to 70-90°C, the feed rate is set to 20-30mL / min, and the atomization pressure is set to 0.3-0.5MPa. The microcapsules are collected and cooled naturally to obtain active component microcapsules.
3. The method for preparing the skin care sunscreen lotion according to claim 1, characterized in that: In S1.3, the oil phase components include cyclopentasiloxane, capric triglyceride, phytosterol esters, titanium dioxide nanoparticles, zinc oxide nanoparticles, octocrylene and avobenzone, and the water phase components include deionized water, glycerin, sodium hyaluronate and witch hazel extract.
4. The method for preparing the skin care sunscreen lotion according to claim 1, characterized in that: The steps of preparing the viscosity stabilizer are specifically as follows: Add xanthan gum to a round-bottom flask containing N,N-dimethylformamide to form a xanthan gum solution. Use a magnetic stirrer to stir at room temperature until it is completely dissolved. Then add 3,4-dihydroxyphenylglycine and continue stirring. Dissolve p-toluenesulfonic acid in N,N-dimethylformamide to form a p-toluenesulfonic acid solution. Add it drop by drop into the mixed solution of xanthan gum and 3,4-dihydroxyphenylglycine while continuing to stir. Transfer the round-bottom flask to a thermostatic oil bath that has been preheated to 50-60°C, turn on the magnetic stirrer, and react for 2 -3h. After the reaction is completed, the round-bottom flask is taken out and cooled to room temperature. Then, a sodium bicarbonate aqueous solution is added, and the mixture after the reaction is poured into a dialysis bag with a molecular weight cutoff range of 1000-2000Da, and dialyzed in deionized water for 72-75h. During this period, the deionized water is replaced every 12-24h. Then, a rotary evaporator is used to remove moisture, and the temperature is set to 30-40°C and the vacuum degree is set to 0.05-0.08MPa. The residue is then transferred to a freeze dryer at minus 40-50°C for drying to obtain a viscous stabilizer.
5. The method for preparing the skin care sunscreen lotion according to claim 4, characterized in that: The mass ratio of the xanthan gum to 3,4-dihydroxyphenylglycine is 1:0.3-0.
5.
6. The method for preparing the skin care sunscreen lotion according to claim 4, characterized in that: The added amount of p-toluenesulfonic acid is 2-6% of the total mass of xanthan gum, and the mass concentration of the p-toluenesulfonic acid solution is 0.4-0.6 g / mL.
7. The method for preparing the skin care sunscreen lotion according to claim 4, characterized in that: The mass concentration of the xanthan gum solution is 0.01-0.03 g / mL.
8. The method for preparing the skin care sunscreen lotion according to claim 4, characterized in that: The molar ratio of the sodium bicarbonate aqueous solution to p-toluenesulfonic acid is 1-1.5:1, and the concentration of the sodium bicarbonate aqueous solution is 0.05-0.1M.
9. A skin care sunscreen lotion, prepared by the preparation method of the skin care sunscreen lotion according to any one of claims 1 to 8.
10. Use of a skin care sunscreen lotion, using the skin care sunscreen lotion according to claim 9 to improve the adhesion of the skin surface.